2022
DOI: 10.1175/jcli-d-21-0805.1
|View full text |Cite
|
Sign up to set email alerts
|

Different ENSO Teleconnections over East Asia in Early and Late Winter: Role of Precipitation Anomalies in the Tropical Indian Ocean and Far Western Pacific

Abstract: This study aims to better understand the ENSO impacts on climate anomalies over East Asia in early winter (November–December) and late winter (January–February). In particular, the possible mechanisms during early winter are investigated. The results show that ENSO is associated with a Rossby wave train emanating from the tropical Indian Ocean toward East Asia (denoted as tIO-EA) in early winter. This tIO–EA wave train in El Niño (La Niña) is closely related to a weakening (strengthening) of the East Asian tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…The North wave train induces an anticyclone formed in the North China, and the South wave train induces a cyclone in the South China. The South wave train is mainly affected by the precipitation anomaly in the eastern Indian Ocean/western Pacific through a double Walker circulation induced by ENSO, which is helpful to the formation of the South wave train (Ma et al, 2022). The North wave train is jointly affected by ENSO, the sea surface temperature over the Labrador Sea and the preceding sea ice over the Kara Sea.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The North wave train induces an anticyclone formed in the North China, and the South wave train induces a cyclone in the South China. The South wave train is mainly affected by the precipitation anomaly in the eastern Indian Ocean/western Pacific through a double Walker circulation induced by ENSO, which is helpful to the formation of the South wave train (Ma et al, 2022). The North wave train is jointly affected by ENSO, the sea surface temperature over the Labrador Sea and the preceding sea ice over the Kara Sea.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Actually, according to previous studies, ENSO may induce a wave train that splits into two branches in Eurasia or cause a strong wave train to spread from mid-high latitudes to eastern China (Sun et al, 2019;An et al, 2022). Ma et al (2022) pointed out that ENSO can induce significant precipitation anomalies in the eastern Indian Ocean/western Pacific through the double Walker circulation, which in turn affects the atmospheric circulations and results in a wave train similar to the South wave train in the upper troposphere. However, ENSO may indirectly have an effect on the North wave train because ENSO can affect the SST over the remote North Atlantic through the effects of atmospheric bridge, which in turn spreads its influences on the East Asian climate.…”
Section: Figurementioning
confidence: 99%
“…Zhao et al (2022) showed that the impact of ENSO on haze pollution over the Beijing-Tianjin-Hebei region is strong in early winter while weak in late winter. Ma et al (2022) further showed that the ENSO-induced anomalous southerly winds along the East Asian coast can extent to mid-and-high latitudes in early winter, whereas those anomalous winds are confined to the subtropics in late winter. Figure 2 shows the 500-hPa geopotential height anomalies over East Asia are distinct different in the early and late winter of the ENSO events.…”
Section: Sub-seasonal Changes In Enso's Signal Over East Asiamentioning
confidence: 93%
“…This northern wave train is reinforced by the positive feedback effect of sea-air coupling over the Mediterranean (An et al, 2022a). It has also been argued that the southern wave train, especially the parts over South and East Asia, can be forced by ENSO (Ma et al, 2022;Zhao et al, 2022). They suggested that precipitation anomalies in the tropical Indian Ocean that associated with ENSO played a crucial role.…”
Section: Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation